Antibody-Proteases in the Pathogenesis of Autoimmune Demyelination and Monitoring Patients with Multiple Sclerosis - Kostyushev, Dmitry; Gnatenko, Dmitry; Paltsev, Mikhail; Gabibov, Aleksandr; Suchkov, Sergey (IntechOpen, 2011)
None